Group I Metabotropic Glutamate Receptor Interacting Proteins: Fine-Tuning Receptor Functions in Health and Disease - Kalinowska, Magdalena; Francesconi, Anna (Current Neuropharmacology, 2016)
Group I metabotropic glutamate receptors mediate slow excitatory neurotransmission in the central nervous system and are critical to activity-dependent synaptic plasticity, a cellular substrate of learning and memory. Dysregulated receptor signaling is implicated in neuropsychiatric conditions ranging from neurodevelopmental to neurodegenerative disorders. Importantly, group I metabotropic glutamate receptor signaling functions can be modulated by interacting proteins that mediate receptor trafficking, expression and coupling efficiency to signaling effectors. These interactions afford cell- or pathway-specific modulation to fine-tune receptor function, thus representing a potential target for pharmacological interventions in pathological conditions.
Keywords: norbin